Electrocoagulation Applied for Removal of Microplastic Polyvinyl Alcohol (PVA) with Aluminium-Aluminium (Al-Al) Electrode in Wastewater - Fardiyah, Qonitah; Ramadani, Azaria Ivana; Rumhayati, Barlah (Universitas Gadjah Mada, 2026)
The use of fabric fresheners and cleaners in the form of laundry capsules has recently received significant attention due to their practicality. The film layer used in the production of laundry capsules is made of plastic derived from polyvinyl alcohol (PVA) as its raw material. The abundance of PVA in domestic waste has led to the increasing presence of PVA microplastic contaminants in aquatic environments. The novelty of this research lies in the use of Al-Al electrodes and the addition of surfactants in the electrocoagulation method for removing PVA microplastics. This study aims to investigate the effect of surfactants on the removal of PVA microplastics in aquatic environments using Al-Al electrodes by electrocoagulation. The parameters evaluated included electrolysis time, voltage, pH, electrolyte type, and electrolyte concentration. The study achieved a PVA microplastic removal efficiency of 93.84% at an electrolysis time of 40 min, with a voltage of 10 V at pH 3, using a 0.01 M NaCl electrolyte solution, as determined by gravimetric analysis. UV–vis yielded a PVA microplastic removal efficiency of 99.52%. Application to synthetic laundry pod samples resulted in a PVA microplastic removal efficiency of 81.97% as determined by UV–vis analysis.